Improvement of Power Quality with Induction Motor in Inertia-Free Stand-Alone Microgrid - Mook Baek, Seung; in Lee, Hee (International Journal of Engineering and Technology, 2018)
This paper proposes a method of improving power quality in inertia-free stand-alone (IFSA) microgrid when induction motor connected. There are many converter based generators (CBGs) in the microgrid. The CBGs has harmonics which affect to induction motor. For smooth operation of induction motor, the input voltage of motor must be pure sinusoidal. The proposed filter design method can mitigate harmonic problem. To verify the proposed method, the IFSA microgrid system is implemented. The induction motor is modelled with dynamic approach to simulate.Â Â